PEMBELAJARAN MATEMATIKA REALISTIK SECARA TEMATIK DI KELAS I SD - Rahmah Johar (Universitas Sriwijaya, 2007)
Based on KTSP, Teaching and Learning in early class is held thematically, it means, some subjects are integrated in a theme. Furthermore, realistic mathematics education needs to be improved in order to make it suitable with curriculum need. The purpose of this research is to improve realistic mathematics teaching materials thematically in the first class of Elementary School. This research was done by classroom action research, which was begun by analyzing problem together with the teacher, and then implemented it for three cycles. The first cycle is limited try out for student in the first class of elementary school, the second cycle is modeling try out for PMRI training participants in Medan, and the third cycle is modeling try out for PMRI workshop participants in Aceh.Â Based on the try out, we got realistic mathematics teaching and learning thematically materials in the first class of elementary school, namely teaching plan and student worksheet. Â Key words: realistics approach, thematics teaching.